PARADIGMA MODERN DALAM RANA PENDIDIKAN ISLAM - Firdaus Firdaus (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2015)
In an effort to reform Islamic education need to be formulated clearly the implications of the verses of the Qur'an and hadith concerning the